NGOs, Political Protest and Civil Society: Book Review - Mahmut Ulas Gozutok (Universitas Diponegoro, 2016)
Non‐governmental organizations (NGOs) play a key role for providing a platform for citizens to raise their discontents in democratic settings. NGO activities for encouraging democratic public engagement pose no threats against stability in consolidated democratic regimes with effectively functioning political parties. On the other hand, they can be acontentious issue in countries with shaky foundations of democracy. In fact, Huntington mainly champions in one of his most widely cited works by the civil society literature the idea that associations of social capital such as civil society can have detrimental repercussions on stability and order in infantile democratic regimes since political parties in such contexts are argued to be ill‐equipped to handle challenges brought bymodernization. On the other hand, primary elements of social capital (i.e.civil society) are acknowledged to be the prerequisites for effectivefunctioning of democracies.Keywords: NGOs, democracy, civil society, social capital